Psychological compatibility and mental health: analytical theory study - Kaoukab Zaman BELYARDOUH; Hayet BEDJA (Social Sciences Journal, 2021)
This theoretical and analytical study aims to shed light on two central concepts in psychology: mental health and psychological compatibility, and to accurately define the ABCs of each concept separately allowing to reveal the Relationship between them. We do not deny that each concept may He received his share of research and study by specialists, that there is an overlap that we touch while trying to determine the relationship between them. Mental health is often defined as the individual’s ability to have a sound psychological compatibility. On the other hand, psychological compatibility is known by the extent to which an individual achieves mental health, but this does not mean that all compatibility Mental health is two sides of the same coin, and accordingly the current study reviews the boundaries of each concept and clarifies the points of participation in the study of both psychological compatibility, health and psychological well-being. Determining the location of both mental health and psychological compatibility, as it provides an integrated view of both of them.